Written text communication strategies among Japanese language learners in Rancangan Persediaan Khas ke Jepun - Ahmad Tajuddin, Farah Nurzakiah (2014)
Writing in a foreign language is a challenge especially for learners in the academic field. However, knowing the most facilitative Communication Strategies (CS) to employ helps learners to overcome language difficulties they face during the writing process. Being the first effort in identifying the facilitative CS in Japanese written text, this study focused on the use of written text CS among Japanese language learners in the Rancangan Persediaan Khas ke Jepun (RPKJ) programme in Universiti Malaya. The objectives of the study were to identify the types of CS in written text employed by the learners, to discuss the most used and moderately used CS and to analyse the differences in the CS employed by the learners in two writing activities. A total of 79 second year RPKJ learners and 72 first year RPKJ learners participated in the study with 10 RPKJ second year learners (high proficiency, HP learners) and 10 RPKJ first year leaners (low proficiency, LP learners) identified as respondents for the writing activities. Using survey questionnaire, a set of writing activities (dialogue and picture description) and a follow-up interview as research instruments, the collected data were analysed and classified according to the inventory of CS presented by Dornyei & Scott (1997). The findings of the study revealed that both HP and LP learners adopted various CS in their written text. Having more Japanese language knowledge, HP learners were able to employ more types of CS as compared to the LP learners. Nonetheless, both groups portrayed themselves to be proactive and attentive learners through their high use of ‘appeal for help’ strategy and ‘self-repair’ strategy. Additionally, the learners used a kanji/kana letter form which was similar looking to the target form which the researcher has named as ‘similar form’ strategy. Relating to the two writing activities, both HP and LP learners utilized the same strategies most in both activities which were ‘self-repair’ strategy and ‘appeal for help’ strategy. However the moderately employed CS reflected the learners’ proficiency level, eventhough the strategies were employed less than ‘self-repair’ strategy and ‘appeal for help’ strategy. This study has highlighted the types of written text CS used by the learners in overcoming their communication difficulties. It is hoped that this study would highlight the facilitative CS in tackling written communication difficulties thus enhancing the language teaching and learning process.